COVID-19 in Oromia Region of Ethiopia: a review of the first 6 months' surveillance data. Issue 3 (29th March 2021) - Gudina, Esayas Kebede; Gobena, Dabesa; Debela, Tessema; Yilma, Daniel; Girma, Tsinuel; Mekonnen, Zeleke; Woldie, Mirkuzie; Abdena, Dereje; Shume, Gemechu; Kenate, Birhanu; Lemi, Meles; Diriba, Dereje; et al.
Abstract : Introduction: Despite unrelenting efforts to contain its spread, COVID-19 is still causing unprecedented global crises. Ethiopia reported its first case on 13 March 2020 but has an accelerated case load and geographical distribution recently. In this article, we described the epidemiology of COVID-19 in Oromia Region, the largest and most populous region in Ethiopia, during the early months of the outbreak. Methods: We analysed data from the COVID-19 surveillance database of the Oromia Regional Health Bureau. We included all reverse transcription-PCR-confirmed cases reported from the region between 13 March and 13 September 2020. Results: COVID-19 was confirmed in 8955 (5.5%) of 164 206 tested individuals. The test positivity rate increased from an average of 1.0% in the first 3 months to 6.3% in August and September. About 70% (6230) of the cases were men; the mean age was 30.0 years (SD=13.3), and 90.5% were <50 years of age. Only 64 (0.7%) of the cases had symptoms at diagnosis. Cough was the most common among symptomatic cases reported in 48 (75.0%), while fever was the least. Overall, 4346 (48.5%) have recovered from the virus; and a total of 52 deaths were reported with a case fatality rate of 1.2%. However, we should interpret the reported case fatality rate cautiously since in 44 (84.6%) of those reported as COVID-19 death, the virus was detected from dead bodies. Conclusion: Despite the steady increase in the number of reported COVID-19 cases, Ethiopia has so far avoided the feared catastrophe from the pandemic due to the milder and asymptomatic nature of the disease. However, with the current pattern of widespread community transmission, the danger posed by the pandemic remains real. Thus, the country should focus on averting COVID-19-related humanitarian crisis through strengthening COVID-19 surveillance and targeted testing for the most vulnerable groups.